Study of particle size on the electrochemical activity of LaNi5 based negative electrodes. - Vỹ, Uông Văn; Hồng, Nguyễn Thị; Quế, Lê Xuân (Vietnam Journal of Chemistry, 2012)
Electrochemical activation process of nano and submicro LaNi3,8Co0,5Mn0.4Al0.3 materials in KOH 6 M solution were studied by cyclic voltammetry. The obtained results show that the materials have been activated after 20 CV cycles. Electrochemical parameters such as E0, Rp, J0, Qn, Qp, bc, ba have been modified together with the particle dimention. The best electrochemical activation arived at 200 nm particles materials.